Silica Content Analysis of Rice Husks Siam Unus from South Kalimantan - Mujiyanti, Dwi Rasy; Ariyani, Dahlena; Lisa, Muna (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2021)
Research on the analysis of rice husk content of Siam Unus with various NaOH concentrations (1.0 M; 1.5 M; 2.0 M; 2.5 M; 3.0 M) has been done. This study aims to obtain data on the effect of variations in NaOH concentration on the purity of the silica extract from Siam Unus rice husks and silica characterization of Siam Unus rice husks using Fourier Transform Infra-Red (FTIR) and X-ray fluorescence spectrometry (XRF). The results showed that the combustion of rice husks at 200 °C as the optimum temperature for 1 hour followed by combustion at 600 °C for 4 hours produces grayish-white rice husks with a yield is 20.70%. Silica functional group characterization showed that silanol (Si-OH) and siloxane (Si-O-Si) as dominant functional groups. The result of composition characterization using XRF showed that SiO2 is the dominant compound with the highest percentage of SiO2 is 1.5 M NaOH extract at 42.80%.